2023
DOI: 10.1007/s00204-023-03558-5
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution and intestinal inflammatory response following voluntary oral intake of silver nanoparticles by C57BL/6J mice

Adelaide Sousa,
Rui Azevedo,
Vera Marisa Costa
et al.

Abstract: Silver nanoparticles (AgNP) are among the most widely commercialized nanomaterials globally, with applications in medicine and the food industry. Consequently, the increased use of AgNP in the food industry has led to an unavoidable rise  in human exposure to these nanoparticles. Their widespread use raises concerns about potential hazards to human health, specifically their intestinal pro-inflammatory effects. Thus, the main objective of this study was to evaluate the biological effects of two subacute doses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
(68 reference statements)
1
0
0
Order By: Relevance
“…Levels of IL-6, IL-12, TNF-α and IL-10 increased across the experimental period and were elevated in both time points. Similar results were described by Sousa et al [44] following 14 days of oral AgNP administration (1 or 10 mg/kg bw) to mice. They observed increased levels of TNF-α and IL-10 in the colon in both doses, as well as an increase in IL-6 and IL-12 treated with the lower, but not the higher dose.…”
Section: Discussionsupporting
confidence: 89%
“…Levels of IL-6, IL-12, TNF-α and IL-10 increased across the experimental period and were elevated in both time points. Similar results were described by Sousa et al [44] following 14 days of oral AgNP administration (1 or 10 mg/kg bw) to mice. They observed increased levels of TNF-α and IL-10 in the colon in both doses, as well as an increase in IL-6 and IL-12 treated with the lower, but not the higher dose.…”
Section: Discussionsupporting
confidence: 89%
“…Numerous animal studies have demonstrated that AgNPs could be found in the intestine after being orally ingested, and the chronic oral exposure to AgNPs damaged the epithelial cell microvilli and increased numbers of goblet cells in the intestine, suggesting that AgNPs may disorder the intestinal immune microenvironment. The accumulation of AgNPs in the intestine can causes inflammation, through damaging the epithelial barrier and activating immune cells. This leads to their infiltration in the intestinal lining, the activation of transcription factors like nuclear factor kappa B (NF-κB), and the release of inflammatory substances such as cytokines and chemokines. , Recent studies reported that the oral exposure of AgNPs can also induce disturbances in the gut microbiota. , Ultimately, these events will contribute to the development or worsening of various gut diseases, such as inflammatory bowel diseases (IBDs, such as Crohn’s disease and ulcerative colitis). Although the toxic effects of AgNPs in the gastrointestinal tract (GIT) have been confirmed, the gastrointestinal fate of AgNPs, including transformation and subsequent cellular interactions, remains not well understood, which is of key importance to assess their health risks. Consequently, an in vitro digestive simulation is necessary to specifically explore the correlation between the transformation and toxicity of AgNPs during gastrointestinal digestion.…”
Section: Introductionmentioning
confidence: 99%